2010
DOI: 10.1016/j.addr.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Beyond oncology — Application of HPMA copolymers in non-cancerous diseases☆

Abstract: Macromolecular drug conjugates have been developed to improve the efficacy and safety profile of various therapeutic agents for many years. Among them, N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer-drug conjugates are the most extensively studied delivery platforms for the effective treatment of cancer. In recent years, the applications of HPMA copolymers for the treatment of a broader range of non-cancerous diseases have also been explored. This review highlights the recent developments in the rational d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 142 publications
2
23
0
Order By: Relevance
“…Wang et al have shown that macromolecular therapeutics preferentially accumulate in inflammatory tissues [99] in general and inflammatory arthritis in particular [91,100,101]. They termed the novel targeting mechanism “ELVIS” (Extravasation through Leaky Vasculature and the subsequent Inflammatory cell-mediated Sequestration) [102,103].…”
Section: State-of-the-artmentioning
confidence: 99%
“…Wang et al have shown that macromolecular therapeutics preferentially accumulate in inflammatory tissues [99] in general and inflammatory arthritis in particular [91,100,101]. They termed the novel targeting mechanism “ELVIS” (Extravasation through Leaky Vasculature and the subsequent Inflammatory cell-mediated Sequestration) [102,103].…”
Section: State-of-the-artmentioning
confidence: 99%
“…Furthermore, HPMA copolymers have recently also been employed to improve the treatment of non-cancerous disorders, such as rheumatoid arthritis and bacterial infections, which are also characterized by a strong inflammation component and leaky blood vessels, and which are therefore also highly amenable to EPR-mediated passive drug targeting [37]. And finally, again primarily for cancer, a significant number of studies have focused on the combination of HPMA copolymer-based nanomedicine formulations with other treatment modalities, such as with surgery, with radiotherapy, with hyperthermia, with photodynamic therapy and with chemotherapy [38,39].…”
Section: Drug Targeting To Tumors Using Hpma Copolymersmentioning
confidence: 99%
“…And finally, again primarily for cancer, a significant number of studies have focused on the combination of HPMA copolymer-based nanomedicine formulations with other treatment modalities, such as with surgery, with radiotherapy, with hyperthermia, with photodynamic therapy and with chemotherapy [38,39]. Together, these insights and efforts, and the wealth of information available in the literature [4][5][6]11,12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], illustrate that HPMA copolymers are highly suitable systems for drug targeting to tumors. In addition, they indicate that by improving the pharmacokinetic and biodistributional properties of attached diagnostic and therapeutic active agents, long-circulating and passively tumor-targeted polymeric drug carriers might be suitable systems for image-guided drug delivery, as well as for improving the efficacy of combined modality anticancer therapy.…”
Section: Drug Targeting To Tumors Using Hpma Copolymersmentioning
confidence: 99%
“…Regarding the former, it is important to note that in recent years, increasing numbers of efforts have been initiated in which therapeutic nanomedicines are used for drug targeting to non-cancerous disorders, including e.g. rheumatoid arthritis and atherosclerosis [12,14,[21][22][23]. As mentioned above, also inflammatory diseases are characterized by leaky blood vessels, and the accumulation of long-circulating nanotherapeutics within such lesions (via 'site-specific drug delivery'), together with their ability to attenuate localization in healthy non-target tissues ('site-avoidance drug delivery'), enables the use of potent anti-inflammatory agents, such as corticosteroids, at much higher i.v.…”
Section: Therapeutic Nanomedicinementioning
confidence: 99%